Face of Fury (A Zoe Prime Mystery--Book 5) - Blake, Pierce (Lukeman Literary, 2020)
"A MASTERPIECE OF THRILLER AND MYSTERY. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) FACE OF FURY is book #5 in a new FBI thriller series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has received over 1,000 five star reviews. FBI Special Agent Zoe Prime suffers from a rare condition which also gives her a unique talent: she views the world through a lens of numbers. The numbers torment her, make her unable to relate to people, and give her a failed romantic life. Yet they also allow her to see patterns that no other FBI agent can. In FACE OF FURY, women are turning up dead, victims of a serial killer who carves a mysterious symbol on their bodies. The symbol holds some mathematical significance, and Zoe struggles to know if he is killing in the order of PI. But when her theory falls apart, Zoe must second guess everything she thought she knew. Has Zoe's talent met its match? And can she save the next victim in time? An action-packed psychological suspense thriller with heart-pounding suspense, FACE OF FURY is book #5 in a riveting new series that will leave you turning pages late into the night.
Keywords: Krimi, detektivky